Prohibition of sexual exploitation of children constituting obligation erga omnes - Malekian, Farhad; Nordlöf, Kerstin (Cambridge Scholars Publishing, 2013)
Whilst the value of human integrity within the laws of individual states and the documents of international human rights is being increasingly consolidated and will become, sooner or later, the primary concern of the law, severe breaches of this value are indeed still widespread. In particular the sexual exploitation of children constitutes one of the most serious questions of national, regional, transnational and international law. According to international records, every fifteen seconds a ...